2009
DOI: 10.1088/0957-4484/20/7/075706
|View full text |Cite
|
Sign up to set email alerts
|

Anin situinvestigation of electromigration in Cu nanowires

Abstract: Electromigration in copper (Cu) nanowires deposited by electron beam evaporation has been investigated using both resistance measurement and the in situ scanning electron microscopy technique. During electromigration, voids formed at the cathode end while hillocks (or extrusions) grew close to the anode end. The failure lifetimes were measured for various applied current densities and the mean temperature in the wire was estimated. Electromigration activation energies of 1.06 eV and 0.94 eV were found for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 24 publications
4
28
0
Order By: Relevance
“…Further, we note that this estimation of the activation energy ( E a ) is independent of the choice of pre-exponential factor ( A ) and current-density exponent ( n ). The value of 2.03 eV was identical to that of Cu lattice diffusion172829 (∼2.0–2.3 eV), which means that the Cu diffusion follows the most difficult pathway. For bulk Cu, diffusion occurs at the surfaces and grain boundaries that possess much lower activation energies172829 (∼0.7 eV and ∼1.0 eV, respectively).…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Further, we note that this estimation of the activation energy ( E a ) is independent of the choice of pre-exponential factor ( A ) and current-density exponent ( n ). The value of 2.03 eV was identical to that of Cu lattice diffusion172829 (∼2.0–2.3 eV), which means that the Cu diffusion follows the most difficult pathway. For bulk Cu, diffusion occurs at the surfaces and grain boundaries that possess much lower activation energies172829 (∼0.7 eV and ∼1.0 eV, respectively).…”
Section: Discussionmentioning
confidence: 58%
“…The value of 2.03 eV was identical to that of Cu lattice diffusion172829 (∼2.0–2.3 eV), which means that the Cu diffusion follows the most difficult pathway. For bulk Cu, diffusion occurs at the surfaces and grain boundaries that possess much lower activation energies172829 (∼0.7 eV and ∼1.0 eV, respectively). Our results showed that for the CNT–Cu composite, the Cu diffusion pathways through surface and grain boundaries were greatly suppressed.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…On the other hand, copper (Cu) nanowires have many useful physical properties, such as their low electrical resistivity and low cost, and they are particularly suitable for *Corresponding author: hyounwoo@hanyang.ac.kr ©KIM and Springer applications in nanodevices [37]. In ultra-large-scale integration (ULSI) circuits, Cu has been widely used for interconnects to reduce the resistance-capacitance delay, the amount of electromigration, and the cost of fabrication [38]. Also, Cu doping has been studied for a variety of applications, including Cu-doped ZnO nanowires for photodetectors [39] and ferromagnetism [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, copper (Cu) nanowires display many useful physical properties; they are particularly suitable for applications in nanodevices owing to their low electrical resistivity and low cost [15]. For example, Cu has been widely used as ultra-large-scale integration (ULSI) interconnects to reduce the resistance-capacitance delay, the amount of electromigration, and the cost of fabrication [16]. Cu doping has been studied for a variety of applications, including Cu-doped ZnO nanowires for photodetectors [17] and ferromagnetism [18,19].…”
Section: Introductionmentioning
confidence: 99%